Effect of Scientific Attitudes and Critical Thinking towards Environment Ability by the Contextual Teaching and Learning Guide with Sets Approach of Seven Grade Students in SMP Negeri 3 Palu - Putrianti, Putrianti; Hatibe, Amiruddin; Kade, Amiruddin (Jurnal Riset Pendidikan MIPA, 2017)
The objectives of the research are to gain information concerning the influence between (1) scientific attitudes towards environmental ability outcome, (2) critical thinking towards environment ability outcome, (3) scientific attitudes together with critical thinking and environment ability outcome. The tested hypothesis indicated that there is a positive influence between (1) scientific attitudes and environment ability outcome, (2) critical thinking and environment ability outcome, and (3) scientific attitudes together with critical thinking and environment ability outcome. The method used was pre-experimental. The targeted populations were all 503 students in seven classes of SMP Negeri 3 Palu with 36 students samples selected by using a simple purposive sampling technique. The technique of collecting data used questionnaires, critical thinking test, and environment ability test. The results showed that: (1) there is a significant influence between scientific attitudes student’s to environment ability through the contextual teaching and learning guide with SETS approach (Fcount 27.095 > Ftable 4.13) with a contribution of 44.3%, (2) there is a significant influence between critical thinking student’s to environment ability through the contextual teaching and learning guide with SETS approach (F count 9.970 > Ftable 4.13) with a contribution of 22.7% (3) there is a significant influence between scientific attitudes and critical thinking student’s to Environment Ability through the contextual teaching and learning models with SETS approach (F count g 13.475 > Fttable 3.30) with a contribution of  45.0%.